2009
DOI: 10.1093/aob/mcp173
|View full text |Cite
|
Sign up to set email alerts
|

Effective pollinators of Asian sacred lotus (Nelumbo nucifera): contemporary pollinators may not reflect the historical pollination syndrome

Abstract: This study indicated that in their pollinating role, beetles, probable pollinators for this thermoregulating plant, had been replaced by some generalist insects in the wild. This finding implies that contemporary pollinators may not reflect the pollination syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 38 publications
1
39
2
Order By: Relevance
“…Natural pollination study In this study, the seed-setting rate of the sacred lotus varied from 52-78% under natural conditions, unlike a previous report which gave a seed-setting rate up to 90% 3 . The lotus seed-setting rate markedly varied among cultivars 3,4 .…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Natural pollination study In this study, the seed-setting rate of the sacred lotus varied from 52-78% under natural conditions, unlike a previous report which gave a seed-setting rate up to 90% 3 . The lotus seed-setting rate markedly varied among cultivars 3,4 .…”
Section: Discussionmentioning
confidence: 64%
“…The lotus seed-setting rate markedly varied among cultivars 3,4 . Many researchers have indicated that the low seed setting in other plants is caused by insufficient pollinators; i.e., pochote (Pachira quinata) 25 , violet (Viola cornuta) 26 , Chinese plums (Prunus salicina) 27 , and lotus (N. nucifera) 3 . Table 2 The self-incompatibility index in RC and NW comparisons of the mean numbers of seed per flower from self-and cross-pollination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations